MODEL ADOPSI DAN PENGGUNAAN ELECTRONIC BANKING (Studi pada Nasabah Pengguna E-Banking di Kota Palembang) - HERI SETIAWAN (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2014)
This study aims to determine the factors that influence the adoption and use of electronic banking. The framework was developed based on the Technology Acceptance Model developed by Davis and the Diffusion of Innovation developed by Rogers and combined with self-efficacy, risk, and trust. This study uses data collected and processed from the list of questions. The population are customers of BCA, Bank Mandiri, Bank BNI in Palembang. Based on the population obtained a sample of 175 respondents. Sample selection techniques using Purposive Sampling method. Analysis using the approach of path analysis that use to explain the value of the independent variable on the dependent variable. The results showed that the perceived ease of use have a positive effect on the intention of use electronic banking. Perceived usefulness have a positive effect on the intention of use electronic banking. self-efficacy have a positive effect on the intention of use electronic banking. Perception of perceived risk negatively affect on the intentions of use electronic banking. Trust have a positive effect on the intention of use electronic banking. Intention of use has a positive effect on the actual use of electronic banking.